Clinacanthus nutans: a review on ethnomedicinal uses, chemical constituents and pharmacological properties - Ihsan N. Zulkipli; Rajan Rajabalaya; Adi Idris; Nurul Atiqah Sulaiman; Sheba R. David (Taylor & Francis Group, 2017)
Context: Medicinal plants have attracted global attention for their hidden therapeutic potential. Clinacanthus nutans (Burm.f) Lindau (Acanthaceae) (CN) is endemic in Southeast Asia. CN contains phytochemicals common to medicinal plants, such as flavonoids. Traditionally, CN has been used for a broad range of human ailments including snake bites and cancer. Objectives: This article compiles the ethnomedicinal uses of CN and its phytochemistry, and thus provides a phytochemical library of CN. It also discusses the known pharmacological and biological effects of CN to enable better investigation of CN. Methods: This literature review was limited to articles and websites published in the English language. MEDLINE and Google Scholar databases were searched from December 2014 to September 2016 using the following keywords: "Clinacanthus nutans" and "Belalai gajah". The results were reviewed to identify relevant articles. Information from relevant selected studies was systematically analyzed from contemporary ethnopharmacological sources, evaluated against scientific literature, and extracted into tables. Results: The literature search yielded 124 articles which were then further scrutinized revealing the promising biological activities of CN, including antimicrobial, antiproliferative, antitumorigenic and anti-inflammatory effects. Few articles discussed the mechanisms for these pharmacological activities. Furthermore, CN was beneficial in small-scale clinical trials for genital Herpes and aphthous stomatitis. Conclusion: Despite the rich ethnomedicinal knowledge behind the traditional uses of CN, the current scientific evidence to support these claims remains scant. More research is still needed to validate these medicinal claims, beginning by increasing the understanding of the biological actions of this plant.